Preparation and Dynamic Mechanic Properties of Surface-Modified Coal Gangue Powder/Styrene-Butadiene-Styrene Composites - Cheng, Guojun; Yu, Xiuhua; Xu, Chuyang (Asian Journal of Chemistry, 2012)
In this work, native coal gangue powders were modified by g-aminopropyltriethoxysilane coupling agent (KH550) and coal gangue powders/styrene-butadiene-styrene composites were prepared by mixing process. The structure and surface properties of modified coal gangue powders were characterized by Fourier transform infrared spectroscopy (FTIR), contact angle measuring instrument and thermogravimetric analysis (TGA). The effect of different dosage of coal gangue powders on coal gangue powders/SBS composites was also systematically studied. It is reported that KH550 can effectively improve the hydrophobic property of coal gangue powders. It can also be found that modified coal gangue powders brings well dynamic mechanical properties to styrene-butadiene-styrene, especially when the dosage is 20 phr and the overall best performance of coal gangue powders/styrene-butadiene-styrene composites can be achieved.